PRINSIP PENDIDIKAN INKLUSIF RASULULLAH : RELEVANSI HADIS DALAM MEMBANGUN PENDIDIKAN RAMAH DISABILITAS - umirul musyarofah; Salwa Hajar; Naila Nafahatus Sahariyah Al-Ulya; Rikza Syahrial Kurniawan; Muhammad Suyudi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Inclusive education is a vital paradigm in establishing an equitable, adaptive, and disability-friendly educational system. Within the Islamic context, the values of inclusive education are neither foreign nor novel; they were already practiced during the prophetic era of the Prophet Muhammad SAW. This study aims to explore the principles of inclusive education reflected in the Prophetic traditions (ḥadīth), particularly those narrated by Imam Tirmidzi Imam Malik in al-Muwaṭṭa’, and Imam Ibn Majah. These narrations illustrate the Prophet’s interactions with companions with disabilities, such as ‘Abdullah ibn Umm Maktūm, and his prophetic attitude in granting them roles, dignity, and religious responsibilities. The research employs a qualitative descriptive approach through content analysis and thematic interpretation to extract contextual meanings from the hadiths. The findings reveal that principles such as recognition of human dignity, functional justice, social empowerment, and structural accommodation of persons with disabilities were foundational to the Prophet’s educational practice. These insights are reinforced by the social model of disability, Amartya Sen’s capability approach, and the Islamic legal framework of maqasid syariah, which upholds the protection of life, intellect, and human dignity as fundamental objectives. The study concludes that integrating prophetic values into the development of inclusive education is highly relevant to transforming the national education system into one that is more humanistic, inclusive, and transformative Keywords: Inclusive Education, Prophetic Hadith, Disability, Maqasid Syariah, Capability Approach, Islamic Humanism